Respostas

2014-03-05T21:16:42-03:00
1)  (-45; -38; -31...)
       r=razão
       r=-38-(-45)=-38+45; r=7
      primeiro termo= a
₁=-45
      termo geral=an an=a1+(n-1)*r ⇒an=(-45)+(n-1)*7
      20º termo     a₂₀=(-45)+(20-1)*7
                          a₂₀=(-45)+19*7
                          a₂₀=(-45)+133
                           a₂₀=88

2)   
( -14/17; -45/34; -31/17;...)
     1º) colocar todos os termos sobre o mesmo denominador
          -14/17=-28/34
          -45/34=-45/34
          -31/17=-62/34
PA=(-28/34, -45/34,-62/34)
 r=razão; r=(-45-(-28))/34 = (-45+28)/34=-17/34
 termo geral an=a
₁+(n-1)*r
                   a₂₀=(-28/34)+(20-1)*(-17/34)
                 
  a₂₀=(-28/34)+19*(-17/34)                   
                  
 a₂₀=(-28/34)+(-323/34)=
                  
 a₂₀=-351/34 ou 10*11/34

3) (1,23; 1,25; 1,27;...)
    a
₁=1,23
    r=1,25-1,23; r=0,02
    termo geral an=a
₁+(n-1)*r
                         an=1,23+(n-1)*0,02
    a
₂₀=1,23+(20-1)*0,02
    a₂₀=1,23+19*0,02
    
a₂₀=1,23+0,38
    a₂₀=1,61
 


   

    


1 5 1